Optimalisasi Dana Zakat dan Pemberdayaan Ekonomi Umat di Indonesia - Dina Arfianti Siregar; Asmuni; Tuti Anggraini (Syntax Literate, 2023)
Zakat as the third pillar of Islam is one of the fundamental things in Islamic teachings. Zakat has a social dimension to become a separate identity that can have a good impact on society, both as an effort to worship Allah and as an effort to social care with fellow human beings. However, zakat is not only limited to having this function. Optimizing the distribution of zakat funds in a professional manner will have a better impact on distribution or income efforts to the community. This study uses a descriptive approach. Data sources are obtained from data in the form of books, articles, and processed data from other parties or publication data, such as BAZNAS publication data and those related to this research in Google Schoolar. The results of this study Zakat, infaq, and alms are a form of worship for a Muslim with the aim of seeking the pleasure of Allah SWT. In carrying out zakat, infaq, and alms can reduce the amount of poverty that exists. Therefore it is necessary to have a management body that manages zakat, infaq, and alms that can manage it properly, and can improve the community's economy.